Low-temperature fabrication of superhydrophobic surfaces with switchable adhesion property based on ZnO nanorod arrays. (2016) - Zhu, Jiyuan; Hu, Xiaofang; Li, Yongli; Xiong, Jingwen
A facile route is reported in this paper to develop superhydrophobic surfaces with controllable water adhesion property based on ZnO nanostructure arrays on metal copper substrate. The rough structure was obtained at normal atmospheric pressure at 35°C. Modified by perfluorooctanoic acid (PFOA), the surfaces were endowed with good superhydrophobic property, showing a static contact angle of water ranging from 151.2° to 154.9° and rolling angle ranging from 5° to 88.5°. The surface adhesion could be adjusted within a wide range. The morphology and crystalline structures of ZnO nanorods were characterised by scanning electron microscopy (SEM), X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR). The adhesion mechanism of the superhydrophobic surfaces is also discussed and the resulting surfaces are subject to several tests to prove the stability of the surfaces and the feasibility of the research method.